KALITUHAYUAN - Ni Kadek Tiana Gangga Dewi; Tjokorda Istri Putra Padmini; Gusti Ayu Ketut Suandewi (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
Kalituhayuan means beatiful. It derives from the word listuayu, thus it is defined as beauty. The dance describes Ni Pollok who is a legong dancer and a painting model of Le Mayure. The creator’s interest in the process of creating Kalituhayuan dance is driven from enviromental factors, in which the creator has been involved in dancing and beome a muse for balinese make up artist.The process of creating the Kalituhayuan dance refers to the method of creating a dance work called angripta sesolahan. This method consists of 5 principle stages, namely ngerencana, nuasen, makalin, nelesin, and ngebah. In structuring this dance work, the creator also collects data from library sources, discography sources and also information sources. Kalituhavuan is a new creation dance that is danced by six female dancers which their body postures resembling the creator. The make-up used is minimalistic stage make-up, and the clothes used are white, brown and red. This work uses the hand fan as a property, which is a characteristic of Legong dance and is shaped like a brush. The dance is accompanied by Gamelan Semara Pagulingan and uses gerong vocals to add the atmosphere in every part. Keywords: Kalituhayuan, Ni Pollok, Model and Legong